Lexical expressions and grammatical markers for source of information: A contrast between German and Korean. (July 2022) - Choi, Soonja; Goller, Florian; Ansorge, Ulrich; Hong, Upyong; Yun, Hongoak
Abstract: Specification of information sources in human speech – evidentiality – prevents misunderstandings and allows listeners to assess the validity of the information communicated. Some of the same linguistic forms used for evidentiality, including grammatical markers and lexical items, are also reported to have a 'mirative' function, and can be used by speakers to express their surprise. Importantly, languages differ in the type of forms they typically use for evidentiality. For instance, corpus analyses suggest that German uses lexical items, while Korean typically encodes evidentiality via grammaticalized sentence-ending (SE) markers. Little is known, however, about the extent to which such linguistic differences are reflected in speakers' use of these forms in verbal interaction. To fill this gap, we carried out an experimental study in which Korean and German speakers were presented with events in audio and/or visual modalities and asked to describe them verbally as well as to rate their degree of surprise about the events. The results revealed several major differences between the two languages. Korean speakers used a high frequency of evidential SE markers, particularly the hearsay marker -tay, while German speakers, who relied on lexical items, encoded evidentiality much less frequently. In Korean, grammatical markers of evidentiality showed pragmatic extensions: The hearsay marker -tay carried an overtone of mirativity. Korean speakers seldom used markers having to do with perception, -te(la) and -ney ; instead, it was the neutral marker -e that correlated with the salience of the visual evidence. In contrast, German speakers encoded hearsay and visual perception with lexical verbs in comparable frequencies, slightly prioritizing visual evidence. In German, lexical expressions ( sagen / hören 'say/hear', sehen 'see') did not show pragmatic extension, and unmarked sentences did not imply a visual information source. These and other findings offer important insight into the lexical-grammatical continuum in evidentiality and the relationship between language and cognition in general. Highlights: The study shows the extent of semantic/pragmatic differences between lexical and grammatical forms for source of information. Evidential particles in Korean have pragmatic extensions, but lexical expressions for source of information in German do not. The hearsay form -tay in Korean has a 'surprise' overtone, but lexical verbs marking hearsay in German ( höre n/sagen) do not. The neutral sentence-ending marker -e in Korean is used more often as visual source of information becomes more salient. German speakers use hearsay and visual perception verbs in comparable frequencies, slightly prioritizing visual evidence.